2007
DOI: 10.1055/s-2007-982518
|View full text |Cite
|
Sign up to set email alerts
|

Gender Specific Correlations of Adrenal Gland Size and Body Fat Distribution: A Whole Body MRI Study

Abstract: The high correlation between the adrenal gland volume and VAT in women underlines the link between hypothalamic-pituitary-adrenal (HPA) axis, stress, and circadian cortisol rhythm, respectively, and an increased abdominal fat volume. The lack of correlation between visceral fat and adrenal volume in men points to an additional influence of sex hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 12 publications
6
16
0
Order By: Relevance
“…If the presence of the specific combination of both high leptin and visceral fat is important for depression to emerge, this combination may be a less important contributing factor for depression in women due to differences in visceral fat levels and related metabolic consequences. Indeed, it has been consistently shown also in the present study that women, as compared to men, have higher measures of body fat but less visceral adiposity (22,23). Visceral adiposity is associated with metabolic disturbances and increased inflammatory response that, in turn, have been linked to depression and development of leptin resistance (2228).…”
Section: Discussionsupporting
confidence: 86%
“…If the presence of the specific combination of both high leptin and visceral fat is important for depression to emerge, this combination may be a less important contributing factor for depression in women due to differences in visceral fat levels and related metabolic consequences. Indeed, it has been consistently shown also in the present study that women, as compared to men, have higher measures of body fat but less visceral adiposity (22,23). Visceral adiposity is associated with metabolic disturbances and increased inflammatory response that, in turn, have been linked to depression and development of leptin resistance (2228).…”
Section: Discussionsupporting
confidence: 86%
“…However, these measures are rough estimates, and investigations of visceral and subcutaneous adiposity in HIV-infected children through more sensitive techniques (such as single-slice CT or MRI) have been limited (16). Although no standards for visceral and subcutaneous fat are available for children, we found that girls have a greater subcutaneous adipose tissue and non-Hispanic whites have greater amounts of visceral fat in our sample, findings that have been substantiated in other non-HIV studies (30)(31)(32). Furthermore, NNRTIs were found to be protective against, yet NRTIs associated with, higher visceral adipose tissue levels.…”
Section: Discussionsupporting
confidence: 73%
“…The body fat distribution, particularly abdominal visceral and subcutaneous adiposity, has been associated with gender-related variation in inflammatory markers, including hsCRP, IL-6, TNF- α , and adiponectin. In fact, fat distribution is known to differ across genders, with men having more visceral and less subcutaneous fat [34]. In our study, even after having adjusted for BMI, we cannot exclude a contribution of abdominal visceral adiposity in men, as manifested by increased WC, for the more prejudicial inflammatory status found relative to women population, which included not only higher TNF- α content but also lower levels of adiponectin.…”
Section: Discussionmentioning
confidence: 83%